PENGARUH CURRENT RATIO DAN TOTAL ASET TURNOVER TERHADAP PERTUMBUHAN LABA PADA PT AKASHA WIRA INTERNASIONAL TBK PERIODE 2013 – 2022 - Fidia Safitri; Bulan Oktrima (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of current ratio and total asset turnover partially on profit growth and to determine the effect of current ratio and total asset turnover simultaneously on profit growth at PT Akasha Wira Internasional Tbk for the period 2013-2022. The research method used in this study is quantitative with a descriptive approach. Data analysis used is descriptive test, classical assumption test, simple and multiple linear regression, determination coefficient, correlation coefficient, and hypothesis test. Based on the results of partial research using the t test, the current ratio has no significant effect on profit growth with a significance value of 0.607> 0.05 with a t count of 0.539 <t table 2.365. The results of the total asset turnover study showed no significant effect on profit growth with a significance value of 0.410> 0.05 with a t count of -0.876 <t table 2.365. The results of simultaneous testing for the influence of current ratio and total asset turnover on profit growth showed no significant influence with a value of 0.118> 0.05 with an Fcount value of 1.459 <Ftable 4.737. The results of the determination coefficient test showed an R Square (R2) value of 29.4%. This is in accordance with the hypothesis test that there is no contribution of the influence of Current Ratio and Total Asset Turnover on Profit Growth.